The Town Plans and Sketches of William Stukeley. (2nd April 2016) - Robson, Brian; Bower, David
Abstract : The eighteenth-century field archaeologist, William Stukeley, travelled widely throughout England to produce the numerous sketches and plans that illustrated his Itinerarium Curiosum . His work has generally not been seen as having made a serious contribution to the cartography or to the portrayal of the towns and landscape of preindustrial England, but the quality of his sketches and the relative accuracy of his town plans are explored here to suggest that this may be too harsh a view.